2009
DOI: 10.1108/00070700910992916
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the ecological soundness of organic and conventional agriculture by means of life cycle assessment (LCA)

Abstract: Purpose: The present study aims to explore and compare consumer perception and scientific evidence related to food quality and food safety aspects of organic versus conventional vegetables.Design/methodology/approach: Primary data on consumer perception were gathered in 2006-2007 through a consumer survey with Flemish adults (n = 529) and compared with scientific evidence from literature. Consumers of organic and conventional vegetables were selected by means of a convenience sampling procedure. Subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 77 publications
4
38
1
Order By: Relevance
“…Table 3 and Table 4 present the average values obtained for each impact category referred to the two functional units used in the study, 1 kg tigernuts and 1 ha, respectively. Unlike the results of previous studies (Backer et al, 2009;Martinez Blanco et al, 2010), no differences can be detected between the average results referred to the two functional units. This is due to the fact that the differences in the yield obtained by the two farming systems are not significant, as commented on section 3.1.…”
Section: 2contrasting
confidence: 56%
See 1 more Smart Citation
“…Table 3 and Table 4 present the average values obtained for each impact category referred to the two functional units used in the study, 1 kg tigernuts and 1 ha, respectively. Unlike the results of previous studies (Backer et al, 2009;Martinez Blanco et al, 2010), no differences can be detected between the average results referred to the two functional units. This is due to the fact that the differences in the yield obtained by the two farming systems are not significant, as commented on section 3.1.…”
Section: 2contrasting
confidence: 56%
“…LCA methodology has proved to be a valuable tool for the environmental evaluation of farming systems. Some agricultural LCA studies have assessed specific agricultural production systems (Sanjuán et al, 2005;Blengini and Busto, 2009;McDevitt and Milà i Canals, 2011); others have compared systems, such as conventional versus organic farming (Meisterling et al, 2008;Backer et al, 2009; Van der Werf et al, 2009;Venkat, 2012). Every one of those studies has addressed the differences between the farming systems regarding environmental impacts.…”
Section: Introductionmentioning
confidence: 99%
“…De Bakker et al [84], examining leeks in Belgium in a full LCA analysis, concluded -that the total climate change indicator score, Global Warming Potential, GWP100 is 0.094 kg CO 2 -equivalents/kg leek for the conventional system and 0.044 kg CO 2 -equivalents/kg leek for the organic system, revealing conventional leek production to have a substantially higher impact on climate change. The GWP depends mainly on the use of fossil fuels for on farm activities, energy use for the production of inputs and emissions of N 2 O connected to the on-farm nitrogen cycle.‖ Diesel use kg -1 leek was actually higher in organic, but the on-farm nitrogen cycle and synthetic fertilizer use in the conventional system had a larger impact than fossil fuel use.…”
Section: Vegetablesmentioning
confidence: 99%
“…LCA has been used since the end of the 1990s to assess the environmental impact of single crop cultivation, and has shifted to various agriculture sectors: animal production, horticulture, organic farming, etc. [1][2][3]. In Europe, it is promoted to certify environmentally-assessed products, and EPD (Environmental Product Declaration) was introduced to reduce the environmental burden of production.…”
Section: Introductionmentioning
confidence: 99%